2021
DOI: 10.1002/hyp.14447
|View full text |Cite
|
Sign up to set email alerts
|

Trend of annual maximum rainfall in Campania region (Southern Italy)

Abstract: Extreme rainfall events are increasing in both number and intensity at global scale; however, it is hard to quantify the impact of climate change at local scale given the strong temporal and spatial heterogeneity of this process. Moreover, limited data availability and its spatial variability requires significant effort to identify specific trends at the regional level. In this study, we attempt to construct a detailed description of rainfall patterns and trends over the Campania region, southern Italy. For th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
3
9
0
Order By: Relevance
“…A substantial improvement in the predictive performance of the indirect sea wave estimations obtained in the present study case can be reached by combining them with the most advanced methods for the quantitative assessment of stochastic uncertainty propagation [65][66][67][68][69][70][71][72], as reported by previous environmental and ecohydraulic engineering studies [73][74][75][76][77][78][79][80]. Finally, as illustrated in Figure 6, in this study, a good correlation was observed between average buoy-based and average satellite-based wave heights (m) over the southern coasts of the Caspian Sea, associated with a slight overestimation in all the examined months.…”
Section: Comparative Analysissupporting
confidence: 60%
See 1 more Smart Citation
“…A substantial improvement in the predictive performance of the indirect sea wave estimations obtained in the present study case can be reached by combining them with the most advanced methods for the quantitative assessment of stochastic uncertainty propagation [65][66][67][68][69][70][71][72], as reported by previous environmental and ecohydraulic engineering studies [73][74][75][76][77][78][79][80]. Finally, as illustrated in Figure 6, in this study, a good correlation was observed between average buoy-based and average satellite-based wave heights (m) over the southern coasts of the Caspian Sea, associated with a slight overestimation in all the examined months.…”
Section: Comparative Analysissupporting
confidence: 60%
“…A substantial improvement in the predictive performance of the indirect sea wave estimations obtained in the present study case can be reached by combining them with the most advanced methods for the quantitative assessment of stochastic uncertainty propagation [65][66][67][68][69][70][71][72], as reported by previous environmental and ecohydraulic engineering studies [73][74][75][76][77][78][79][80].…”
Section: Comparative Analysissupporting
confidence: 59%
“…Few previous studies have been dedicated to the characterization and to the analysis of the precipitation regime of this area (Avino et al, 2021; Califano et al, 2015; Longobardi & Boulariah, 2022; Longobardi & Villani, 2010). According to the results of those works, in the period from 1918 to 2015, the annual precipitation in Campania region shows a general negative trend, although statistically relevant only for a very limited number of stations.…”
Section: Methodsmentioning
confidence: 99%
“…The main novelties of this work can be synthesized in the two following key‐points: For the first time, the complete set of ETCCDI indices and the SPI have been applied to a dataset of daily rainfall measurers collected in the Campania region. Although several previous studies have been devoted to this area (Avino et al, 2021; Califano et al, 2015; Longobardi & Boulariah, 2022; Longobardi & Villani, 2010), none of them has employed a wide and complete spectrum of precipitation indices to fully characterize the complex variability of extreme rainfall events in terms of frequency, intensity and duration. The reference period of our work includes the last two decades (2002–2021), which were the hottest on the global scale in the instrumental period (Skea et al, 2022). According to a very recent study (Rodell & Li, 2023), an increase of global total intensity of extreme events (including both floods and droughts), mirroring the Earth's rising temperature, occurred between 2002 and 2021.…”
Section: Introductionmentioning
confidence: 99%
“…The spatial interpolation of the best estimates was taken as a possible alternative to the proposed hybrid regional procedure for estimating the mean annual maximum rainfall at sub-hourly durations at sites where only an hourly time resolution database existed. Among other alternatives, spatial interpolation of rainfall maxima with ordinary kriging [30,31] was chosen as it is a valid technique and widely employed in the literature (i.e., [32,33]); Other geostatistical methods such as co-kriging and universal kriging were tested as well, however, their use was discarded after no significant correlations were found between sub-hourly mean annual rainfall maxima and other auxiliary external topographic variables such as elevation [34]. The performance of the kriging estimator was assessed by means of the cross-validation method [21,31,32].…”
Section: Performance Estimationmentioning
confidence: 99%